Brutal highlanders and crooked seasiders : two opposing Mediterranean literary archetypes - Bešker, Inoslav (Array, 2020)
This paper presents a philological and imagological analysis of the mutual contradictions of two types of characters in the corpus of Mediterranean literature. The highlander and the seasider, one brutal and the other imbedded in the hetero-conception of the other, belong to standard Mediterranean literary types, namely archetypes, from myths to the present. Literature on the Mediterranean and about the Mediterranean is abundant with typified descriptions of the highlander being a tough guy, violent, and the seasider as cunning, envious or a serial seducer. The imagology of these types and their mutual opposition is the topic of this philological analysis. The paper focuses on a comparative analysis of this imagotype/stereotype existing throughout the Mediterranean and transmitted from one literature to another throughout the centuries. The aim of the work is to review and summarize the literature concerning the archetypes of the highlander and the seasider in order to have a better understanding of the patterns of imagotypes and archetypes in the collective imaginary represented by Mediterranean literature.